1982
DOI: 10.1073/pnas.79.4.1316
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of guanylate cyclase within neurons of rat brain.

Abstract: The immunohistochemical localization of guanylate cyclase [GTP pyrophosphate-lyase (cyclizing), EC 4.6.1.2] has been examined in rat neocortex, caudate-putamen, and cerebellum by using specific monoclonal antibodies. Immunofluorescence could be seen within somata and proximal dendrites of neurons in these regions. A nuclear immunofluorescence reaction to guanylate cyclase was characteristically absent. Guanylate cyclase [GTP pyrophosphate lyase (cyclizing), EC 4.6.1.2] catalyzes the formation of guanosine 3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(50 citation statements)
references
References 21 publications
4
45
0
1
Order By: Relevance
“…Neuronal NO synthase is found in parallel fibers but not in Purkinje cells and climbing fibers (Rodrigo et al 1994). In contrast, expression of soluble guanylate cyclase is restricted to Purkinje cells (Ariano et al 1982). NO released from parallel fibers evokes cGMP generation in Purkinje cells by soluble guanylate cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal NO synthase is found in parallel fibers but not in Purkinje cells and climbing fibers (Rodrigo et al 1994). In contrast, expression of soluble guanylate cyclase is restricted to Purkinje cells (Ariano et al 1982). NO released from parallel fibers evokes cGMP generation in Purkinje cells by soluble guanylate cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…A postsynaptic expression of the phenomenon thus appeared more likely, but required a trans-synaptic messenger. In the search for such a messenger, we took into account reports of the presence of NO synthase (NOS) in PFs (24), of NO production by these fibers (25), and of a body of observations suggesting that NO released by the PFs can activate the soluble guanylate cyclase (sGC) expressed by the PCs (26,27) and trigger a postsynaptic decrease in the glutamate sensitivity of ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors. This trans-synaptic signaling pathway has been most systematically described in the analysis of cerebellar long-term depression (ref.…”
Section: Resultsmentioning
confidence: 99%
“…Early biochemical studies (see Ferrendelli, 1978, for a review of the older literature), immunocytochemical studies (Ariano et al, 1982;Chann-Palay and Palay, 1979;Nakane et al, 1983), and mRNA in situ hybridization studies (Burgunder and Cheung, 1994;Giulli et al, 1994;Matsuoka et al, 1992) all show a wide spread occurrence of sGNC in the CNS. In addition, immunocytochemical studies on NO-mediated cGMP production demonstrated structures capable of synthesizing cGMP in almost all parts of the central and peripheral nervous system (De Vente and Steinbusch, 1992;Hopkins et al, 1996;Shuttleworth et al, 1993;Smet et al, 1996;Southam and Garthwaite, 1993;Young et al, 1993).…”
Section: Introductionmentioning
confidence: 97%